2015
DOI: 10.1038/srep10439
|View full text |Cite
|
Sign up to set email alerts
|

Neurological morphofunctional differentiation induced by REAC technology in PC12. A neuro protective model for Parkinson’s disease

Abstract: Research for the use of physical means, in order to induce cell differentiation for new therapeutic strategies, is one of the most interesting challenges in the field of regenerative medicine, and then in the treatment of neurodegenerative diseases, Parkinson’s disease (PD) included. The aim of this work is to verify the effect of the radio electric asymmetric conveyer (REAC) technology on the PC12 rat adrenal pheochromocytoma cell line, as they display metabolic features of PD. PC12 cells were cultured with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
(38 reference statements)
1
36
0
Order By: Relevance
“…It was also found that 1800 MHZ exposure of mouse embryonic neural stem cells, with a specific absorption rate (SAR) of 4 W/kg, could decrease neurite outgrowth [23]. Lately, another team evidenced that radio electric asymmetric conveyor (REAC) technology, involving a 2.4 GHz exposure (SAR = 0.128 W/kg), induced a shift of the exposed PC12 cells toward the neurogenic phenotype, characterized by an increased protein expression of the neuronal marker βIII-tubulin [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that 1800 MHZ exposure of mouse embryonic neural stem cells, with a specific absorption rate (SAR) of 4 W/kg, could decrease neurite outgrowth [23]. Lately, another team evidenced that radio electric asymmetric conveyor (REAC) technology, involving a 2.4 GHz exposure (SAR = 0.128 W/kg), induced a shift of the exposed PC12 cells toward the neurogenic phenotype, characterized by an increased protein expression of the neuronal marker βIII-tubulin [24].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 , 41 ]). In addition, experimental field studies indicate a profound role for complex interactions across scales governing community dynamics [ 19 , 42 , 43 ]. The MEM-framework offers a quantitative approach towards understanding scale-dependent community interactions associated with abiotic variables (also see, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Compounding this picture, electromagnetic fields have been shown to afford neurological and morphofunctional differentiation in PC 12 cells [40], a rat adrenal pheochromocytoma cell line displaying metabolic features of Parkinson's disease. The action of electromagnetic fields was mediated by the transcriptional activation of neurogenic genes, as neurogenin-1, β3-tubulin and nerve growth factor (NGF), and was associated with a consistent increase in the number of cells expressing both β3-tubulin and tyrosine hydroxylase [40].…”
Section: S4mentioning
confidence: 99%
“…The action of electromagnetic fields was mediated by the transcriptional activation of neurogenic genes, as neurogenin-1, β3-tubulin and nerve growth factor (NGF), and was associated with a consistent increase in the number of cells expressing both β3-tubulin and tyrosine hydroxylase [40]. More recently, we have shown that the antiaging effect of REAC conveyed electromagnetic fields could be significantly opposed by stem cell exposure to an inhibitor of type 2 hyaluronan synthase (HAS2) [41].…”
Section: S4mentioning
confidence: 99%